Systematic review: learning styles as a strategy for elaboration of courses in the modality of distance education in higher education (Research, Society and Development, 2020)
The article presents a Systematic Literature Review (RSL), whose objective was to investigate the learning styles, in the modality of Distance Education (DE), in students of higher education and teachers in training. Such studies are in line with the perspective of developing pedagogical strategies that take into account the learning styles of this group, making virtual and / or personal environments personalized. RSL followed a protocol to identify relevant studies, selecting 51 articles from 2013 to 2018, and submitted to the inclusion and exclusion criteria, resulting in 07 articles for analysis. Regarding the results, there are investigations that seek to gather contributions that show the importance of knowledge of students' learning styles, in their strengths or weaknesses. It is concluded that this approach can contribute to the design of distance courses in a generalized way, considering the individual differences of the learners.